The Legal Protection for Notaries against Civil Efforts on Authentic Deeds That Have Been Published - Saputra, Rizal Alamsyah Hadi; Bawono, Bambang Tri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Notaries have carried out their responsibilities in accordance with applicable regulations by using the principles of vigilance and prudence, but still have to deal with legal issues because provisions are also permissible, and it is feared that distrust will arise in the authentic deed made before a notary and the credibility of a notary in the jurisdiction Merauke Regency is also in doubt. This study aims to find out and analyze the legal standing of deeds that have been issued by a Notary when a lawsuit is filed by the parties and to find out and analyze the legal protection for a notary against civil proceedings for authentic deeds that have been issued in Merauke Regency (case study no. 80/ pdt. bth/2021/pn/mrk). The approach method in this research is a sociological juridical approach. Based on the research, it was concluded that legal protection for Notaries in case decisions Number 80/PDT.Bth/2021/PN/MRK The Panel of Judges is of the opinion that a credit agreement is an agreement between the debtor and the creditor to bind himself in the provision of debts and receivables which can be done by the debtor providing guarantees or without guarantees for repayment of debts to creditors. If there is collateral in the credit agreement, it is an additional agreement with the credit agreement as the main agreement, with these agreements applying as a law for the makers according to the provisions of Article 1338 of the Civil Code if it has been legally made by fulfilling the legal requirements of the agreement as stipulated in Article 1320 Civil Code. Keywords: Civil; Efforts; Notary; Protection.